Violência institucional no âmbito da saúde reprodutiva : a percepção de mulheres usuárias do SUS, na cidade de Natal/RN - Melo, Carmen Oliveira Medeiros (2007)
Institutional violence ranges from the most widespread lack of access to the poor quality of services provided. It includes abuses committed by virtue of the unequal power between patients and professionals within institutions. The aim of this study was to analyze the perception of women with regard to this type of violence, in the services offered at a reproductive health facility belonging to the National Health System (SUS) in Natal, Brazil. Interdisciplinary perspective is important, in that it provides interaction and complementarity between various disciplines, favoring, in an integrated way, a thematic approach in research activities, teaching and extension, involving professionals, students and researchers in medicine, social services, psychology, nursing, anthropology and physical therapy. A quantitative/qualitative approach was used, involving a sample of 401 women, as part of a transversal observational study. In the qualitative stage, which consisted of participatory observation and semi-structured interviews, we used an intentional sample of 10 individuals. The data were analyzed using logistic regression techniques, correspondence analysis and categorical thematic content analysis, showing that the 2 questions that investigated directly the perception of institutional violence obtained affirmative response frequencies of 28.2% and 31.8%, respectively. In regard to data collected in a field diary related to participatory observation, the main complaints referred to the health providerpatient relation, translated into dissatisfaction with the interpersonal relationship and with the resolution of the specific demand that required care. From content analysis, we classified 4 categories: Access; Information; Health professionalpatient relation; and Respect/dignity. We identified 6 subcategories: Impossibility of choice; Repressed demand; Communication difficulty; Asymmetric interpersonal relations; Privacy/confidentiality; Disrespect. We concluded, therefore, that the data presented show that in the reproductive health care programs, there are indicators of institutional violence. However, it is difficult to approach this phenomenon, mainly because of the power relations involved in the patient-health care provider interaction, resulting from unawareness that determinate situations violate sexual and reproductive rights. This can be explained by sociostructural questions that reveal marked inequalities, ratified by issues related to violation of the rights of National Health System (SUS) patients